PERANAN KELUARGA DALAM MENANAMKAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM KEPADA ANAK - Zulhaini Zulhaini (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2019)
Abstract The family was first child educational environment. In the neighborhood kid has the right to the influence of the family first of all , because that is the family are the institutions highest education informal in nature .This is kid has the right to the care of families from the parents of the indonesian currency to reach its development .Before a child know the environment , the community , other school and to the outer world .He first influenced by his family especially environment his parents .In the family , every parents wants children who she had given birth to be among the progressing in a perfect .They certainly seek to make child who was born into a smart man , as well as be speech to those who believe in god .It means very simple insecurity , some parents do not wants her kid to be the generation that mischievous and far from the values of religious education. Islam is a religion that was very care to education .Implemented the system of islamic education along hayat , as the word of it came to which means “ demand that the knowledge from the cradle until liang lahad” .If we will take a look at this in an upright position and disbelief in him is stated that occurred in early education in family .We can understand that the first time a child getting an education from her family .The first thing is very important implanted in yourselves sons of the in the process of education first this is planting religious values .Is very important as early as possible in yourselves sons of the basic must be built strong religious provide financial support for him to lived his life. Keywords: The Role of the Family, the Values of Islamic Education in Children